Beginning PHP and MySQL 4th Edition - Gilmore, W. Jason (Apress, 2012)
Great programming books dwell more in the realm of the practical than of the academic. Although I have no illusions regarding my place among the great technical authors of our time, it is always my goal to write with practicality in mind, providing instruction that you can apply to your own situation. Given the size of this book, it's probably apparent that I also tried to squeeze out every last drop of such practicality from the subject matter. That said, if you're interested in gaining practical and comprehensive insight into the PHP programming language and MySQL database, and how these prominent technologies can be used together to create dynamic, database-driven web applications, this book is for you. The feverish work of the respective PHP and MySQL communities prompted this new edition—and with it considerable changes over the previous version. In addition to updating the material to reflect features found in the latest PHP and MySQL releases, you'll find a new chapter introducing the concept of AJAX and the popular jQuery JavaScript library. Furthermore, all existing chapters have been carefully revised, and in some cases heavily modified, in order to both update and improve upon the previous edition's material. If you're new to PHP, I recommend beginning with Chapter 1, because it's likely that first gaining fundamental knowledge will be of considerable benefit when reading later chapters. If you know PHP but are new to MySQL, consider beginning with Chapter 25. Intermediate and advanced readers are invited to jump around as necessary; after all, this isn't a romance novel. Regardless of your reading strategy, I've attempted to compartamentalize the material found in each chapter so you can quickly learn each topic without having to necessarily master other chapters beyond those that concentrate on the technology fundamentals.